The (misleading) role of animal models in drug development - Thomas Hartung; Thomas Hartung (Frontiers Media S.A., 2024)
Animals like mice and rats have long been used in medical research to help understand disease and test potential new treatments before human trials. However, while animal studies have contributed to important advances, too much reliance on animal models can also mislead drug development. This article explains for a general audience how animal research is used to develop new medicines, its benefits and limitations, and how more accurate and humane techniques-alternatives to animal testing-could improve this process.